Indicadores de sostenibilidad institucional de energía y gases efecto invernadero en el Centro Experimental, Académico (CEASA) de la Universidad Técnica de Cotopaxi, 2021 - Moposita Toapanta, Jimena Anabel (2021)
This research project aimed to develop indicators of institutional sustainability in the Experimental and Academic Salache Center and the Technical University of Cotopaxi, to reduce atmospheric emissions in energy management. According to what was analyzed, the most significant problem in the institution is the excessive consumption of energy, which implies high economic expenses, and that there are months in which consumption increases notably. Regarding atmospheric emissions, it does not exceed the permissible limits of 150 ug / m3 where the value obtained is 11.20 ug / m3, which is established in the Ecuadorian air quality standard, however a projection of higher years because there will be an increase in students and vehicles entering the University. Previous studies were evaluated, one from 2014 on electricity consumption and the second from 2019 on air quality. Based on these results, 20 institutional sustainability indicators were established, which will help control and mitigate the effects that they may cause with the passing of the years, considering the 2030 sustainable development objectives. The applied methodology was based on bibliographic research such as journals, theses, academic articles related to institutional sustainability, jointly, the inductive and deductive methods were used, which provided the selection of indicators according to some guidelines that are applied and studied in the research area. Finally, a strategic plan was developed where is intended to use alternatives that are viable and help strengthen the University, with the activities proposed for each indicator to involve the university community to participate in environmental programs in order to achieve a sustainable campus in addition to obtaining a certification or recognition of sustainability for the University.